Osteoimmunology - Choi, Yongwon (Springer, 2017)
Schnurri-3: A Key Regulator of Postnatal Skeletal Remodeling -- Ectodomain Shedding of Receptor Activator of NF-κB Ligand -- The Negative Role of Ids in Osteoclastogenesis...